Blood flow-restricted training and time trial performance: A cohort study of world-class rowers - Thompson, K. M. A.; Pethick, W. A.; Clarke, J.; Winegarden, A.; Johnson, E.; Coates, A. M.; Stellingwerff, T.; Burr, J. F. (Medicine & Science in Sports & Exercise, 2024)
Introduction This study aimed to explore the potential impact of incorporating blood flow restriction (BFR) training within a training block characterized by minimal high-intensity work on 2000-m rowing ergometer time trial (TT) performance in elite/world-class rowers. Physiological markers often associated with endurance performance (maximal aerobic capacity, VO2max; blood lactate thresholds and hemoglobin mass, Hbmass) were measured to determine whether changes are related to an improvement in performance.